Students’ Interpersonal Communication in Building Closeness With Lecturers and Fellow Students in The Digital Era - Ratna Ekawati; Eko Prasetyo Nugroho Saputro; Gilang Jiwana Adikara; Anugerah Tesa Aulia; Arselma Trus'tee Audrey (Universitas Negeri Yogyakarta, 2025)
This study aims to examine how interpersonal communication among Communication Science students at Universitas Negeri Yogyakarta contributes to building relationships with lecturers and peers, as well as to identify factors influencing its effectiveness in both face-to-face and digital contexts. This research employed a qualitative approach.The informants were Communication Science students from the 2022, 2023, and 2024 cohorts, selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis with source triangulation to ensure data validity. The findings indicate that face-to-face communication is perceived as more effective in fostering openness, empathy, supportiveness, positivity, and equality due to the presence of nonverbal cues and immediate feedback. Digital communication, meanwhile, functions as a complementary medium that offers flexibility and accessibility, particularly for academic information exchange. The effectiveness of interpersonal communication is influenced by message clarity, constructive feedback, appropriate and polite language use, relational equality, empathy, emotional closeness, timing, and flexibility in digital communication. This study highlights the importance of integrating face-to-face and digital communication to establish effective and harmonious academic relationships in higher education.